Argentina chiama Italia: Friuli risponde (Altre Modernità, 2010)
The study analyzes the migratory waves from Friuli which, from the 1870s up to the post-World War II years, extensively moved towards Argentina, settling in the areas around the cities of Santa Fe, Cordoba, Entre Ríos, Chaco and Buenos Aires, but reaching also regions as far away as Patagonia. The accurate and well diffused net of the Fogolār Furlan, besides its function as friendly society, also provides to the promulgation of ancient traditions and mores among the new generations, transmitting on to them the cultural, linguistic and ethnic memory of the motherland. Epistles, tales, novels and poems form a paideia which is thus constantly being enlivened, eveng among those who assumed Argentinian nationality or were born in the country. Of utmost interest is, therefore, the resulting literary corpus, representing as it does a renewed search for identity in the form of a dialogue with the world, extending itself well beyond the contingency of boundaries and transmitting the universal essence of logos.
Keywords: Migrazioni Friuli Argentina